Vedantic wisdom and contemporary management - Mathur, Krishna Mohan (1999)
Surveying briefly the philosophy of Vedanta and its principles which impinge on contemporary management practice and behaviour of managerial personnel, the author attempts to draw a matrix of these. He then identifies basic challenges that confront management today and offers solutions thereof as per Vedantic wisdom. He follows it up with transformational effects of Vedantic teachings on spiritual, personal, social and organisational levels for the benefit of managers and workers engaged in management. - Reproduced
Keywords: Management